Laughing awry : Plautus and tragicomedy - Gunderson, Erik (Oxford University Press, 2015)
'Laughing Awry' offers a comprehensive overview of key themes in the interpretation of the plays of Plautus, and explores the connections between deception, desire, slavery, genre, and audience. It attempts to offer an account of the mechanisms of Plautus' humour and the uncomfortable origins of laughter